Reorganisasi Remaja Masjid Kepenghuluan Lenggadai Hulu Kecamatan Rimba Melintang Kabupaten Rokan Hilir - Nasrul Fatah; Syarifah Laili; Siti Aisyah (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service activity aims to form a Mosque Youth organization and develop creative work programs as an effort to foster the character of the younger generation in Kepenghuluan Lenggadai Hulu. The method used is Participatory Action Research (PAR), which emphasizes the active participation of youth and the community in every stage of the activity, from problem identification, planning, implementation, to evaluation. The identification results show that there is no structured youth organization forum that hinders the participation and development of the potential of the mosque's younger generation. Activities are carried out through the formation of a Mosque Youth organizational structure with a clear division of tasks (chairman, secretary, treasurer, field coordinator) and the preparation of an annual work program. The initial program carried out in the form of competitions in commemoration of Islamic holidays, including Al-Qur'an memorization competitions, adhan, children's Muslim fashion shows, and coloring Islamic pictures. The program was attended by 45 participants and received a positive response from the community, and was able to increase youth participation in prospering the mosque. This service shows that the formation of participatory-based youth organizations, accompanied by relevant and creative work programs, can be an effective strategy in reactivating the role of the mosque as a center for fostering the younger generation of Islam.